Caracterización filogenética y toxicológica de una cepa de Microcystis aeruginosa productora de Microcystinas aislada del ambiente - Sedan, Daniela (2012)
Cyanobacteria often form dense blooms in freshwater bodies worldwide. Some genera such as Microcystis spp., can synthesize toxic metabolites called microcystins (MCs). The MCs are hepatotoxic cyclic peptides that represent a serious problem for human and animal health. We report the identification, and phylogenetic and Toxicological characterization for the first strain of Microcystis aeruginosa Argentina(CAAT2005) isolated from the environment and maintained under culture conditions. Morphological characterization shows the typical colonial architecture of Microcystis aeruginosa. Further phylogenetic analysis based on the sequence-ISM cpcBA confirms the identity given grouping with known sequences of strains of M. aeruginosa. The strain of Microcystin CAAT2005 expresses a toxin variant, common in samples from the basin of the Salado river and La Plata basin, having a molecular ion [M + H] + = 1037.8 m / z was identified by LC-HRMS / Orbitrapas as [D-Leu 1] microcystin-LR. This is the first strain of Argentine toxigenic cyanobacteria maintained under controlled growth conditions. The available national and international laboratories to study and compared with strains from around the world, as well as for technological development and production of analytical standards that correspond to variants of toxins that occur in our region.